Cross-modal interactions between olfaction and touch. - Demattè, M; Sanabria, D; Sugarman, R; Spence, C (2006)
We report two experiments designed to investigate the nature of any cross-modal interactions between olfactory and tactile information processing. In Experiment 1, we assessed the influence of olfactory cues on the tactile perception of fabric softness using computer-controlled stimulus presentation. The results showed that participants rated fabric swatches as feeling significantly softer when presented with a lemon odor than when presented with an animal-like odor, demonstrating that olfactory cues can modulate tactile perception. In Experiment 2, we assessed whether this modulatory effect varied as a function of the particular odors being used and/or of the spatial coincidence between the olfactory and tactile stimuli. The results replicated those reported in Experiment 1 thus further supporting the claim that people's rating of tactile stimuli can be modulated by the presence of an odor. Taken together, the results of the two experiments reported here support the existence of a cross-modal interaction between olfaction and touch.